Кәмил инсан болып жетилисиўде дене тәрбия ҳәм спорттың әҳмийети (SCIENCE and SOCIETY, 2022)
The article deals with the role of the national struggle in the formation of national pride among the youth. The significance of the na- tional struggle in the spiritual preparation of the youth is scientifically substantiated. The struggle is also considered as factors that serve to strengthen national characteristics.